Mejora para la Orientación educativa a padres de niños de 7 a 10 años con TDAH, en el Centro Psicoterapéutico La Cabaña” periodo 2023 -2024. - González Castro, Daniela Alejandra (2024)
Inattention, hyperactivity, and impulsivity are the hallmarks of attention deficit hyperactivity disorder (ADHD), which is divided into three categories based on the most common symptoms: impulsivity, hyperactivity, and/or inattention (ADD), or a combination of both. Kids with ADD often have trouble organizing their work, paying attention to details, and following directions. This can lead to distractions and forgetfulness during everyday activities. The family is an essential source of learning and a socializing agent. By establishing behavioral, moral, and attitudinal norms, parents provide their children with ADHD with a vital support system. To improve educational and psychological approaches and to educate and include all family members in the care of these children, family counseling is essential. Implementing educational guidance tools for parents of children at the La Cabaña Psychotherapeutic Center in Loja was the objective of this integrative work. A quasi- experimental, quantitative, descriptive study was carried out, with the use of observation guides and interviews. Most of the parents had a high degree of ignorance about ADHD, according to the data, but after the intervention their conceptual errors were reduced and they reached a sufficient level of knowledge. This demonstrates how family counseling techniques help the psychoeducational growth of children with ADHD and improve their quality of life.